The experience of community health workers training in Iran: a qualitative study - Javanparast Sara; Baum Fran; Labonte Ronald; Sanders David; Rajabi Zohreh; Heidari Gholamreza (BMC, 2012)
Abstract Background The role of Community Health Workers (CHWs) in improving access to basic healthcare services, and mobilising community actions on health is broadly recognised. The Primary Health Care (PHC) approach, identified in the Alma Ata conference in 1978, stressed the role of CHWs in addressing community health needs. Training of CHWs is one of the key aspects that generally seeks to develop new knowledge and skills related to specific tasks and to increase CHWs' capacity to communicate with and serve local people. This study aimed to analyse the CHW training process in Iran and how different components of training have impacted on CHW performance and satisfaction. Methods Data were collected from both primary and secondary sources. Training policies were reviewed using available policy documents, training materials and other relevant documents at national and provincial levels. Documentary analysis was supplemented by individual interviews with ninety-one Iranian CHWs from 18 provinces representing a broad range of age, work experience and educational levels, both male and female. Results Recognition of the CHW program and their training in the national health planning and financing facilitates the implementation and sustainability of the program. The existence of specialised training centres managed by district health network provides an appropriate training environment that delivers comprehensive training and increases CHWs' knowledge, skills and motivation to serve local communities. Changes in training content over time reflect an increasing number of programs integrated into PHC, complicating the work expected of CHWs. In-service training courses need to address better local needs. Conclusion Although CHW programs vary by country and context, the CHW training program in Iran offers transferable lessons for countries intending to improve training as one of the key elements in their CHW program.